Motivations of Cajanus Cajan producers in Benin: A versatile crop facing abandonment despite its multiple uses - Akpo, Ibidon Firmin; Tassou, Filikibirou Zakari; Issaka, Kassimou; Houessingbe, Zachee; Dededji, Nanyegbe Aimee (Asian Journal of Agriculture and Rural Development, 2025)
This study examines the motivations of the few Cajanus cajan producers in Benin, a versatile and highly beneficial crop that receives little institutional support. Using a random sample of 240 producers from the Collines department, it applies Cronbach’s Alpha to assess the internal consistency of their motivations. The resulting composite index was modeled using Seemingly Unrelated Regression (SURE) to analyze the determinants of this motivation. The findings reveal that the selling price, nutritional value, high market demand, high household food needs, declining soil fertility, and the predominance of weeds and pests are the factors with a strong contribution to the decision and action to produce Cajanus cajan. Farmers are more motivated by push factors than by pull factors, indicating that constraints play a more important role in their decision to cultivate this crop than opportunities. Age, literacy, formal education, membership in a group, farm size, and household size are the main determinants of the motivation to cultivate Cajanus cajan. These results suggest adapting agricultural interventions to local realities by valorizing the benefits of Cajanus cajan and creating attractive economic opportunities, such as access to credit and promotional projects, targeting young people and the most educated farmers in particular.